2013
DOI: 10.2478/s13382-013-0147-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of GDP, spending on R&D, the number of universities and scientific journals on research publications in environmental sciences in the Middle East

Abstract: Objectives: This study aimed to assess the impact of the Gross Domestic Product (GDP), spending on Research and Development (R&D), the number of universities and scientific journals on the published research documents, citable documents, citations per document and H-index in environmental sciences in the Middle East countries. Materials and Methods: All the 16 Middle East countries were included in the study. Information regarding the GDP, spending on R&D, the total number of universities and indexed journals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 6 publications
0
24
0
Order By: Relevance
“…In seeking explanation for these findings, the most possible one may be related to high prevalence of cases with WNV in these countries which experienced several outbreaks [45,70,71]. Another possible clarification for these results could be attributed to spending on research and development, gross domestic product per capita, indexed scientific journals, number of universities, and a good utilization of resources for these countries assigned to research output [72][73][74]. Another important finding was that the USA also has the highest h-index, which demonstrated that WNV publications originating from the USA had the highest quality.…”
Section: Discussionmentioning
confidence: 95%
“…In seeking explanation for these findings, the most possible one may be related to high prevalence of cases with WNV in these countries which experienced several outbreaks [45,70,71]. Another possible clarification for these results could be attributed to spending on research and development, gross domestic product per capita, indexed scientific journals, number of universities, and a good utilization of resources for these countries assigned to research output [72][73][74]. Another important finding was that the USA also has the highest h-index, which demonstrated that WNV publications originating from the USA had the highest quality.…”
Section: Discussionmentioning
confidence: 95%
“…References are cited for many reasons, including objects of research and the research content [36]. Citable documents and citations per document were used to assess publications in environmental sciences in some research [37]. Due to the fact that the impact factor is not the most ideal indicator reflecting the quality of papers, this paper employed impact factor, citations and numbers of reference as standards to evaluate the quality of publications.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore essential to quantify current research output as it constitutes the basis for strategic planning and decisions making [7]. Bibliometric analysis, now a widely accepted method for assessing research in many fields, is employed to quantify and assess research output and also depict its growth and spread [8].…”
mentioning
confidence: 99%